CLOUD-ORIENTED LEARNING TOOLS IN THE PROCESS OF DESIGN AND TECHNOLOGICAL ACTIVITY OF STUDENTS - Данник, Людмила; Перегудова, Валентина (Modern engineering and innovative technologies, 2023)
The article reveals the expediency and necessity of implementing tools based on cloud technologies in the process of project-technological activities of students in labor training lessons, provides characteristics of the most popular Google services for u